2006
DOI: 10.1377/hlthaff.25.5.1319
|View full text |Cite
|
Sign up to set email alerts
|

Benefit Design And Specialty Drug Use

Abstract: In this paper we examine spending by privately insured patients with four conditions often treated with specialty drugs: cancer, kidney disease, rheumatoid arthritis, and multiple sclerosis. Despite having employer-sponsored health insurance, these patients face substantial risk for high out-of-pocket spending. In contrast to traditional pharmaceuticals, we find that specialty drug use is largely insensitive to cost sharing, with price elasticities ranging from 0.01 to 0.21. Given the expense of many specialty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 6 publications
(3 reference statements)
1
92
0
Order By: Relevance
“…[3][4][5][6] GH is an example of the fastest growing class of pharmaceuticals: expensive biological specialty drugs, many with controversial indications and unclear end points for treating chronic conditions. [6][7][8][9][10] This study addresses current gaps in the literature by systematically investigating endocrinologists' recommendations for GH treatment of ISS, and assesses (1) the relative influence of guidelines, patient preferences, and physician beliefs on recommendations to initiate GH, and (2) the determinants of physician decisions to continue GH unchanged, intensify GH (increase mg/kg dose), or terminate GH in children after a course of treatment, including the roles of treatment response, family wishes, pretreatment factors, attitudes, and contextual factors.…”
mentioning
confidence: 99%
“…[3][4][5][6] GH is an example of the fastest growing class of pharmaceuticals: expensive biological specialty drugs, many with controversial indications and unclear end points for treating chronic conditions. [6][7][8][9][10] This study addresses current gaps in the literature by systematically investigating endocrinologists' recommendations for GH treatment of ISS, and assesses (1) the relative influence of guidelines, patient preferences, and physician beliefs on recommendations to initiate GH, and (2) the determinants of physician decisions to continue GH unchanged, intensify GH (increase mg/kg dose), or terminate GH in children after a course of treatment, including the roles of treatment response, family wishes, pretreatment factors, attitudes, and contextual factors.…”
mentioning
confidence: 99%
“…Multi-tiered plans are the standard in the United States (Goldman 2006), with 89% of covered workers in 2010 belonging to a plan with a tiered cost-sharing formula for prescription drugs (Kaiser Family Foundation 2012). In contrast, only 19% of Canadian employees with drug benefit plans appear to have managed formularies, suggesting this might be a major opportunity for reducing private sector drug costs, again without limiting patients' access to medicines.…”
Section: Discussionmentioning
confidence: 99%
“…Specialty drugs are becoming increasingly popular, including some that can cost hundreds of thousands of dollars every year (Goldman 2006;Kim et al 2011). If this trend continues, it is likely that many Canadians, including those with chronic conditions, will hit these benefits limits.…”
Section: Discussionmentioning
confidence: 99%
“…This is evidenced by the elasticities (percentage change in use associated with a 1% increase in effective coinsurance rates) of specialty drug use by patients among 4 conditions: rheumatoid arthritis, kidney disease, multiple sclerosis, and cancer. For example, Goldman et al 19 reported that if an insurance plan were to double the cost of sharing for rheumatoid arthritis specialty drugs, overall spending on these drugs would decrease by 21%. However, for cancer drugs, spending would be decreased by only 1%.…”
Section: Why Are Cancer Drugs So Expensive?mentioning
confidence: 99%